2011
DOI: 10.1007/s12154-011-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into structure and function of SHIP2-SH2: homology modeling, docking, and molecular dynamics study

Abstract: SRC homology 2 (SH2)-containing inositol 5′-phosphatase protein (SHIP2) is a potential target for type 2 diabetes. Its ability to dephosphorylate the lipid messenger phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P3], important for insulin signaling, makes it an important target against type 2 diabetes. The insulin-induced SHIP2 interaction with Shc is very important for the membrane localization and functioning of SHIP2. There is a bidentate relationship between the two proteins where two domains each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As a negative regulator of PI(3,4,5)P3 level, SHIP2 inhibition in liver cancer cells enhances PI3K/AKT signaling and prevents ROS production after palmitate treatment [29], whereas its overexpression suppresses PI3K/AKT signaling and cell growth in gastric cancer cells [27]. SHIP2 and PTEN are the major negative regulators of PI3K/AKT signaling [18–20], and both proteins are highly expressed in cervical cancer cell lines HeLa and SiHa (Fig. 1A and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a negative regulator of PI(3,4,5)P3 level, SHIP2 inhibition in liver cancer cells enhances PI3K/AKT signaling and prevents ROS production after palmitate treatment [29], whereas its overexpression suppresses PI3K/AKT signaling and cell growth in gastric cancer cells [27]. SHIP2 and PTEN are the major negative regulators of PI3K/AKT signaling [18–20], and both proteins are highly expressed in cervical cancer cell lines HeLa and SiHa (Fig. 1A and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN dephosphorylates the three-position phosphate of PI (3,4,5)P3 and Phosphatidylinositol (3,4)-bisphosphate (PI(3,4)P2) to generate, respectively, PI(4,5)P2 and PI4P, and this event results in suppression of AKT signaling [18]. SHIP2 dephosphorylates the five-position phosphate from PI (3,4,5)P3 to generate PI(3,4)P2, leading also to inhibition of AKT-mediated signaling pathways in response to growth factor like insulin [19,20]. Previous studies have shown that SHIP2 plays a role in regulation of PI3K-dependent insulin signaling [21][22][23].…”
mentioning
confidence: 99%
“…The structures of the 5-phosphatase domain and the SAM domain of SHIP2 have been well studied [2730]. However, although a 3D model of SHIP2 SH2 domain was described previously [31], the experimental structure had not yet been reported. In this study, we determined the solution structure of SHIP2-SH2 domain using NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Ligand-based virtual screening approach was used in here to calculate the lowest binding energy between α-glucosidase enzyme with ligand and also to study their binding affinity 16 . We chose the enzyme α-glucosidase C-neutral protein in humans as the target for virtual screening [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%